Penguatan Karakter Jujur Pada Anak Usia Dini Melalui Dongeng Pinokio - Mutiara, Arda Sulis; Muzakki (Beujroh : Jurnal Pemberdayaan dan Pengabdian pada Masyarakat, 2024)
This community service is motivated by the understanding that strengthening the character of honesty during the early stages of child development is crucial, as it represents a golden phase that should be effectively utilized. One of the methods explored is using the story of Pinocchio to reinforce honesty in early childhood. This community service program was conducted in October 2024 at Darul Istiqomah Islamic Kindergarten, Palangka Raya. The program aims to observe how the exploration of the Pinocchio story can serve as a tool to strengthen honesty in children, using the Service Learning (SL) approach. The steps taken include analysis, program planning, activity implementation, reflection and evaluation. The sample used consisted of 26 children from group B. The results indicate that the story of Pinocchio can enchance children’s understanding of the importance of honesty in daily life. The children realize that speaking the truth brings goodness and that honesty is a trait valued by Allah SWT. Furthermore, they understand that lying leads to wrongdoing and sin. Thus, using the story of Pinocchio has proven effective as a means to strengthen honesty in children’s character development, demonstrated through a qualitative (empirical) approach using observation and discussion ad evaluation tools.